1978
DOI: 10.1063/1.325124
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional numerical simulation of ac discharges in a high-pressure mixture of Ne+0.1% Ar confined to a narrow gap between insulated metal electrodes

Abstract: The dynamics of a highpressure ac gas discharge between dielectric coated electrodes near breakdown threshold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…There have been many one-and two-dimensional numerical models of PDP discharges over the last a few years. [2][3][4][5][6][7] One-dimensional models are sufficient for simulating matrix-type PDP, [2][3][4] while the study of coplanar-type PDP requires at least two-dimensional modeling. [5][6][7] Because of its low speed, three-dimensional simulations are not common, though three-dimensional variations of the cell structure are widely performed in experiments.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many one-and two-dimensional numerical models of PDP discharges over the last a few years. [2][3][4][5][6][7] One-dimensional models are sufficient for simulating matrix-type PDP, [2][3][4] while the study of coplanar-type PDP requires at least two-dimensional modeling. [5][6][7] Because of its low speed, three-dimensional simulations are not common, though three-dimensional variations of the cell structure are widely performed in experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9]. Sahni and Lanza [2] reported the first detailed PDP model, which was a one-dimensional fluid code, and their simulation results showed a satisfactory agreement with measured parameters.…”
Section: Introductionmentioning
confidence: 53%
“…[2][3][4][5][6][7][8][9]. Sahni and Lanza [2] reported the first detailed PDP model, which was a one-dimensional fluid code, and their simulation results showed a satisfactory agreement with measured parameters. Boeuf et al [3,4] developed a two-dimensional fluid code, and found that a non-negligible part of the xeon excitation in a PDP discharge occurs in the anode region, during the spreading of the plasma along the dielectric surface above the anode.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…There have been many numerical models of PDP discharges over the last few years. [10][11][12][13][14][15][16][17][18] One-dimensional models are sufficient for simulating matrix-type PDP, [10][11][12] while the study of coplanar-type PDP requires at least two-dimensional ͑2D͒ modeling. [13][14][15] The three-dimensional ͑3D͒ variations of the cell structure require 3D models.…”
Section: Introductionmentioning
confidence: 99%